(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The features of the antropophytes participation in the natural and semi-natural steppe coenoses were investigated on the territory of Burgunska beam. (Kherson region, Ukraine). On its slopes there are pockets of indigenous steppe vegetation of class Festuco-Brometea Br.-Bl. et R.Tx. in Br.-Bl. 1949. But the anthropogenic transformation of the steppe biome led to penetration in steppe community of alien species. According to the results of our research they represented 64 species, which belong to 59 genera, 24 families, 15 orders. Most of the investigated alien plants belong to mesophytic group and gemiagriophytes. They are well naturalized in the communities of meadow vegetation, that’s why they grow in the thalweg of the beam. The greatest numbers of diasporas of these species falls with the water streams from agrophytocenoses and they are representatives of the classes segetal vegetation Stellarietea mediae and Artemisietea vulgaris.